Strategi Guru Dalam Meningkatkan Motorik Kasar Anak Usia Dini Umur 4-5 Tahun Di TKQ al Istiqomah Kedokan Bunder - Faziyah, Muidatul; Saomi, MuhamadRizka; Imron, Imron (Iftitiah: Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2025)
Gross motor skills are the ability to move the body using the muscles of most or all of the body parts which are influenced by the child's age, weight and physical development. Early sensorimotor learning is the basic building block for more complex perceptual and cognitive development. The research objectives at TKQ al-Istiqomah Kedokan Bunder are: 1) to determine early childhood gross motor development; 2) to determine the forms of teacher activities in developing early childhood gross motor skills; 3) to find out the teacher's strategy in improving children's gross motor skills. Researchers use a qualitative approach with this type of case study research. The data collection techniques in this study used observation, interview and documentation techniques. The data analysis technique is by reducing data, presenting data, and drawing conclusions. The research results show that: 1) Gross motor development at TKQ al-Istiqomah Kedokan Bunder according to the results of researchers' observations from 12 children, 1 developed according to expectations (BSH) and 11 children began to develop (MB); 2) The forms of gross motor activities carried out by teachers at TKQ al-Istiqomah Kedokan Bunder are activities that train children's large muscles with their concentration abilities such as doing gymnastics activities, walking through obstacles, throwing and catching balls, running, hanging and 3) Teacher's strategy in Developing early childhood gross motor skills at TKQ al-Istiqomah Kedokan Bunder is a) Set an example for children to imitate; b) Assistance for children. concentrate and justify if something goes wrong; c) Repetition so that the child is able and used to it. Based on the results of observations by researchers at TKQ al-Istiqomah Kedokan Bunder, children are not yet fully able to control their gross motor skills well and perfectly.